Assessment of Employees’ Competences in the System of Professional Qualifications in a Digital Economy - E. P. Pecherskaya (Учёт. Анализ. Аудит, 2019)
In the strategy of socio-economic development of the Russian Federation until 2020, the Development Strategy of the Samara Oblast until 2030, the Development Strategy of Samara until 2025, the tasks are set to transfer the country’s economy to an innovative development path, putting it on the course of fast and sustainable growth on the advanced technological foundation. Regulatory documents focus on innovative and technological development of production, increasing technological initiatives, building a society with a highly developed digital economy. Human resources are the most important intellectual and professional resource that ensures the successful implementation of these strategies. The article substantiates the need to integrate international experience in the assessment of qualifications, as well as it examines the existing system of assessment of qualifications of workers in Russia. It also proposes a logical-structural matrix for linking the professional standards of Russia and Belarus with the countries of the European Union.